2023
DOI: 10.1097/iop.0000000000002314
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Involvement in Multiple Myeloma

Abstract: Purpose: To characterize clinical and radiographic features, management, and outcomes of patients with orbital involvement of multiple myeloma (MM). Methods: A retrospective chart review identified patients with MM and orbital involvement confirmed by histopathology at a single institution between 1995 and 2021. A comprehensive literature review was performed via PubMed to identify all previously reported cases of orbital MM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…[16] It has been indicated that most patients are willing to accept appointment nursing services and are willing to pay the related costs. [17] Some scholars have also pointed out that the readmission rate of patients who participate in the hospital's "Internet + Nursing Platform" for nursing appointments is significantly lower, and the medical cost is lower. [18] Continuous nursing includes the continuation of nursing services and the maintenance of the doctor-patient relationship, and "Internet + Nursing" provides patients with more specialized home care through specialized nursing services from point to point.…”
Section: Discussionmentioning
confidence: 99%
“…[16] It has been indicated that most patients are willing to accept appointment nursing services and are willing to pay the related costs. [17] Some scholars have also pointed out that the readmission rate of patients who participate in the hospital's "Internet + Nursing Platform" for nursing appointments is significantly lower, and the medical cost is lower. [18] Continuous nursing includes the continuation of nursing services and the maintenance of the doctor-patient relationship, and "Internet + Nursing" provides patients with more specialized home care through specialized nursing services from point to point.…”
Section: Discussionmentioning
confidence: 99%
“…An updated, comprehensive literature review in 2023 identified 111 total cases of orbital involvement of multiple myeloma, of which 8 (7.2%) involved the lacrimal gland. 4 Among orbital structures, the lacrimal gland is rarely affected. 6 Prior reports of lacrimal gland involvement do exist but they notably differ from the case presented here in that the affected patients also demonstrated other sites of disease.…”
Section: Discussionmentioning
confidence: 99%
“…An updated, comprehensive literature review in 2023 identified 111 total cases of orbital involvement of multiple myeloma, of which 8 (7.2%) involved the lacrimal gland. 4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations